Assessing Non-material Damages under the GDPR: A Review of The Recent Judicial Practice of Germany, UK, and the Netherlands - Akefi GHAZIANI, Vahid; Akefi GHAZIANI, Moosa; Akefi GHAZIANI, Mohammad (Revista Jurídica Portucalense, 2022)
With the digitalisation of technologies, the issue of the valuation of non-material damages that has long been debated among the courts and scholars is taken more seriously. Although according to the General Data Protection Regulation (GDPR) and its recitals, data controllers are liable for such damages. However, there is inconsistency regarding the interpretation of this instrument, in terms of the scope of damages as well as their assessment. Frustratingly, still, there is no unique rule of compensation laid out for the measurement of non-material damages. Hence, an analysis of the judicial practice of different courts in European countries is important. This Article examines the recent approaches to the valuation of non-material damages under the GDPR, in three European countries, namely, Germany, the UK, and the Netherlands. It pursues to answer the key question that do the courts in these jurisdictions award compensation for non-material damages, and how are these non-pecuniary damages valuated? To answer this question, this article, in two parts, expounds on the concept of non-material damages under the GDPR, and analyses the respective judicial practices of Germany, the UK, and the Netherlands. It concludes that, so far, the approach of the German courts has been unique in the sense of substantiating the broad interpretation of damages in accordance with the GDPR. This legal system has delineated a promising achievement by establishing an implied limitation of liability clause (Lol) which may be equally followed by other European courts.